Lung abscess complicating ventilator-associated pneumonia caused by extensively drug-resistant Acinetobacter baumannii - Amit Kumar; Rajesh Chetiwal; Neha Rana; Aman Dubey; Shweta Tanwar (Exploration of Medicine)
Ventilator-associated pneumonia (VAP) is a common and serious complication in critically ill patients, particularly those requiring prolonged mechanical ventilation. Extensively drug-resistant (XDR) Acinetobacter baumannii has emerged as a significant threat in VAP cases, complicating treatment due to its exceptionally high level of antibiotic resistance. We present a case of a 62-year-old male patient with severe acute ischemic stroke, who developed VAP during his stay in the intensive care unit (ICU). Cultures confirmed XDR Acinetobacter baumannii as the causative organism. The infection was further complicated by the development of a lung abscess, a rare but severe consequence of VAP. The patient was treated with a targeted antimicrobial regimen consisting of colistin, vancomycin, and tigecycline. Despite the pathogen’s resistance profile, the patient’s infection showed gradual improvement with sustained treatment. However, the recovery process was significantly prolonged due to the complexity of the infection, necessitating extended supportive care during hospitalization. This case highlights the challenges posed by XDR infections in critically ill patients and the importance of a tailored antimicrobial approach to effectively manage severe complications such as lung abscess.